Sexual Dimorphism in Finger Ridge Breadth Measurements: A Tool for Sex Estimation from Fingerprints. Issue 4 (19th February 2014) - Mundorff, Amy Z.; Bartelink, Eric J.; Murad, Turhon A.
Abstract Previous research has demonstrated significant sexual dimorphism in friction ridge skin characteristics. This study uses a novel method for measuring sexual dimorphism in finger ridge breadths to evaluate its utility as a sex estimation method from an unknown fingerprint. Beginning and ending in a valley, the width of ten parallel ridges with no obstructions or minutia was measured in a sample of 250 males and females (N = 500). The results demonstrate statistically significant differences in ridge breadth between males and females (p < 0.001), with classification accuracy for each digit varying from 83.2% to 89.3%. Classification accuracy for the pooled finger samples was 83.9% for the right hand and 86.2% for the left hand, which is applicable for cases where the digit number cannot be determined. Weight, stature, and to a lesser degree body mass index also significantly correlate with ridge breadth and account for the degree of overlap between males and females.